Effect of summer shoot tip pruning and early winter de-flushing on flowering, fruit yield and quality of litchi (Litchi chinensis) - KUMAR, RAJESH (The Indian Journal of Agricultural Sciences, 2015)
The present study was undertaken at the National Research Centre on Litchi, Muzaffarpur, Bihar for two consecutive years 2011-12 and 2012-13 in the young bearing litchi (Litchi chinensis Sonn.) orchard of cv. Shahi to see the effect of shoot tip pruning and de-flushing on reproductive behaviour and fruit yield in litchi. This study confirmed the treatment of shoot tip pruning in mid June evoked maximum number of panicles (41.8% during 2011, 50.5% during 2012-13), causing maximum phase change under the annual production cycle, leading to maximum flowering (860.8 and 1004.3 nos./panicle) with moderately higher fruit set (2.11 % and 4.22%) and highest fruit yield (19.4 kg/tree and 31.9 kg/tree), the pronounced effect recorded when treatment of flush removal applied during mid November, which bore maximum number of panicles (47.3% during 2011-12, 64.3% during 2012-13), maximum flowering (1110.0 nos and 898.5 nos of flowers /panicle) with moderately higher fruit set (3.17% and 4.14 %) and highest fruit yield (25.5 kg/tree and 27.9 kg/tree) in litchi during both the years. Shoot tip pruning in late summer (mid July and mid August) and flush removal in December had virtually poor crop yield since most of the de-flushed branches did not projected a flush of either type of vegetative or reproductive growth before the normal time of even panicle emergence. The study also showed that the age of the previous flush modifies with the cool-temperatureinduced floral response during winter season, while older stems exhibited a higher percentage of reproductive growth by phase change in the form of panicle emergence. The operation of flush removal in mid October displayed only a higher percentage of a vegetative growth and while de-flushing in December projected no growth or if any only vegetative nature. The treatment having pruning in mid June and practice of uniform size and aged (5-8cm) flush removal in the month of November (mid) exposed to low temperature under the conditions of north Bihar leading to highest fruit yield (37.75 kg/tree) and better quality fruits (38.42 % under extra class) with minimum wastage.